Dimensi Pembelajaran Afektif - Pipit, Pipit Pitriah Ulfah (Journal Of Education, 2024)
Affective learning is one of the important dimensions of learning. The affective dimension relates to learners' attitudes, values, interests and emotions. Affective learning plays an important role in shaping learners' character and personality. In this paper, we will discuss the definition, characteristics, and dimensions of affective learning. In addition, it will also discuss the importance of affective learning and affective learning strategies that can be applied by teachers. Keywords: affective learning, affective dimensions, affective characteristics, affective importance, affective learning strategies